FREQUENCY OF HEPATIC LIPIDOSIS IN JUVENILE RAINBOW TROUT (ONCORHYNCHUS MYKISS) IN A FISH FARM IN THE PERUVIAN CENTRAL SIERRA - Rosenthal N., Sandra (2013)
The objective of the study was to determine the frequency of hepatic lipidosis in rainbow trout (Oncorhynchus mykiss) of juvenile phase based on anatomical and histopathological lesions in the liver. The specimens (n=58) were obtained from a commercial fish farm in the central highlands of Peru. The fish were classified as healthy (n=23) and ill (n=35) according to the darkening of the skin and fin erosion. Liver samples were collected, fixed in 10% formalin, and stained with hematoxylin eosin. Results showed that 70.6% (41/58) of the fish had lesions compatible with hepatic lipidosis, where grade 3 had the largest incidence (27.6%). The highest frequency of hepatic lipidosis in grade 3 and 4 was observed in healthy animals.